(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In Shashi Deshpande’s novel, Dark Holds No Terror the traumatic memories of childhood haunts Saru, a reputed doctor, to the extent that she fails to come to terms with her present life. Her present life is devastated not only because of the disturbingly past memories with her late mother, which makes her feel ‘abandoned’, but also because she could perceive the fissures in her marriage. Subject to domestic violence in spite of her strong position in society, she realises that she could counter her present lapses only if she could counter, interrogate and resist the difficult memories of her past, i.e.; ‘return to’ those memories and grasp them to her comprehension. The paper would make an attempt to analyse how Saru articulates the narratives of her traumatic past memories to counter and resist oppression in all aspects of her life and free herself from the shackles of those traumatic memories. Her narrative reflects the culturally silenced stories, memories and pain of almost every woman, and counter memory gives voice to what has been traditionally silenced. Thus, the paper would traverse this inward journey of Saru from ‘return of’ difficult memories to ‘return to’ difficult memories and pave a new way to women’s narrative, memories and identities.